Matilda - Dahl, Roald; Illustrated by Blake, Quentin (New York Puffin Books, 1989)
Matilda is a very clever little girl. Very clever. But her parents and her headmistress have no time for all that, and they make Matilda very cross. So cross, in fact, that she discovers she has a magical power that she can put to very good use on some very unpleasant deserving people.
Include Illustrations
Keywords: Humorous stories